Development of Artificial Intelligence Regulations and Implications for Intellectual Property Rights Protection - Salle Salle; Wafia Silvi Dhesinta Rini (Contemporary Issues on Indonesian Social Justice and Legal Reform, 2025)
his study aims to explore the development of regulations governing artificial intelligence (AI) and their implications for intellectual property (IP) protection. The research employs a normative legal approach, utilizing legislative, conceptual, and comparative methodologies to examine current regulatory frameworks and identify gaps in the protection of AI-generated works. By analyzing the legal landscapes of the United States, European Union, Japan, and China, the study provides a comprehensive overview of how different jurisdictions are addressing the challenges posed by AI in the context of IP law. The findings indicate significant discrepancies in how AI-generated content is treated across these regions, with most existing IP laws requiring human authorship and inventorship, thereby excluding AI-generated works from protection. This gap poses challenges for innovation and raises ethical and social concerns about the future of creativity and employment. The study suggests the need for new legal categories or a sui generis system that offers specific protections for AI-generated content. Additionally, it underscores the importance of stakeholder engagement and international cooperation in developing balanced and effective regulatory frameworks. The research concludes that continuous adaptation of IP laws is essential to keep pace with the rapid advancements in AI technology. Theoretical implications highlight the necessity of rethinking traditional IP concepts, while practical implications emphasize the importance of clear, consistent regulations to foster innovation and provide legal certainty. The study's comparative approach offers valuable insights into best practices and potential areas for harmonization, contributing to the development of global standards for AI and IP protection.